Cultural behaviors as drivers in green bond issuance - Hólmfríður Kristín Árnadóttir 1990- (2020)
This study seeks to answer what drives the Nordic nations to perform better compared to other markets on green bonds issuance. A comparative study using Hofstede’s dimensional approach was conducted to understand which cultural behavioral factors encourage environmental actions and increase the likelihood of green bonds issuance. The results concluded that the cultural factors that are most dominant in affecting the issuance of green bonds in the Nordic countries are the uncertainty avoidance and masculinity factors. With the purpose of obtaining a more transparent result of cultural drivers in relation to the green bond market, the Nordic countries were compared to seven other countries. The results from further comparisons revealed that the nations with the lowest masculinity scores have the highest issuance of green bonds relative to GDP. On the opposite side of the spectrum, the nations with the lowest issuance of green bonds compared to GDP have the highest masculinity scores. In-depth semi-structured interviews were conducted with individuals with experience in the green bond market in Iceland with the intention of obtaining a better overview of the Icelandic market and determine the current status and potentials in the green bond market in Iceland. The main result of the overview is that the Icelandic market is immature and in its very early stages with an associated lack of knowledge. However, the market seems to be growing, both when it comes to interested issuers and investors becoming more aware and willing to develop a focused green investment policy. There are many positive signs surrounding green bonds compared to other conventional bonds in Iceland, but it is too early to draw conclusions based on those signs due to the lack of maturity of the market.